Digital transformation and AI integration in accounting education: Evidence from Albania - Çika, Nertila (Edelweiss Applied Science and Technology, 2025)
The ongoing digital transformation of higher education has profoundly reshaped accounting pedagogy, redefining how knowledge is delivered, assessed, and applied in professional practice. As Artificial Intelligence (AI) and Information Technology (IT) increasingly influence learning environments, universities face the dual challenge of modernizing their curricula while maintaining educational quality and ethical integrity. This study investigates how AI and IT integration enhance teaching and learning outcomes in Albanian universities, focusing on the mediating role of digital literacy and the moderating influence of institutional support. Using a mixed-method design, the research combines quantitative survey data from 215 respondents (170 students and 45 instructors) with qualitative interviews of academic leaders. Statistical analysis employing PROCESS models (4 and 7) validates the conceptual framework and confirms that AI–IT integration improves student performance directly (H1) and indirectly through digital literacy (H2), while institutional support partially moderates this relationship (H3). Reliability (α = 0.87) and factor diagnostics ensure methodological rigor. The findings emphasize that successful digital transformation in accounting education depends not only on technological infrastructure but also on human capacity, leadership engagement, and ethical use of AI tools. By aligning its implications with the EU Digital Education Action Plan (2021–2027), this study contributes practical guidance for higher-education institutions seeking sustainable modernization and serves as a replicable model for other transitional economies in the Western Balkans and beyond.